Characterization of Fish Skin Hydrolysates Exhibiting Dipeptidyl Peptidase IV Inhibitory Activity - Miyamoto, Honoka; Safitri, Erwina; Nagai, Takeshi; Saito, Masataka (Indonesian Association of Food Technologists, 2024)
Dipeptidyl peptidase IV (DPP-IV) inhibitors are antidiabetic drugs that can lower blood sugar levels. There are still few reports on the DPP-IV inhibitory activity of peptides obtained from discarded fish skin. Therefore, we prepared various enzymatic hydrolysates using the skins of six fish species and investigated their DPP-IV inhibitory effects. As a result, it was found that the DPP-IV inhibitory activity of yellowtail hydrolysate by Alcalase was higher than that of other enzymes. In addition, the IC50 after ethanol fractionation was found to be lower in yellowtail and eel skin hydrolysate. Amino acid composition analysis showed that the hydrolysate obtained from the skin of the yellowtail contained the highest amount of Gly, followed by Pro, Hyp, and Ala, indicating that it was a peptide derived from type I collagen. Fractionation with ethanol showed that the DPP-IV inhibitory components were contained in the low molecular weight fraction. The artificial digestion test observed no DPP-IV inhibitory activity or average molecular weight change. The DPP-IV inhibitory peptide obtained from fish skin has the potential to be applied as a food material to various food products.